Gagasan Teologi Perdamaian Hassan Hanafi terhadap Gerakan Islam Di Indonesia - Asy’ari (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2020)
The issues of radical Islamic movements in Indonesia cannot be separated from that of the Islamic movements in the Middle East. Hassan Hanafi also did not escape the radar that he was one of the seeds of progressive revolutionary Islamic thinkers. Hassan Hanafi as one of the Ikhwanul Muslimin activists and identified as one of the actors of the rebellion of his time. Hassan Hanafi, through hisrevolutionary Islamic Left, is very fertile in the world of movement activists in Indonesia. This paper seeks to see and explain Hassan Hanafi from another perspective. In Hassan Hanafi's thought, there is a horizon that can be an offer in sowing peace in the middle of a revolutionary Islamic movement in Indonesia. The author sees that the proliferation of revolutionary Islamic movements that quoteHassan Hanafi's thoughts is due to the lack of comprehensiveness in reading this horizon.